The SAMI galaxy survey: gas velocity dispersions in low-z star-forming galaxies and the drivers of turbulence - Varidel, Mathew; Croom, Scott M.; Lewis, Geraint F.; Fisher, Deanne B.; Glazebrook, Karl; Catinella, Barbara; Cortese, Luca; Krumholz, Mark R.; Bland-Hawthorn, Joss; Bryant, Julia J.; Groves, Brent; Brough, Sarah; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. We infer the intrinsic ionized gas kinematics for 383 star-forming galaxies across a range of integrated star formation rates (SFR ∈ [10−3, 102] M⊙ y